A Mead‐Chomsky Comparison Reveals a Set of Key Questions on the Nature of Language and Mind. (27th August 2013) - Gallagher, Timothy J.
Abstract The social psychologist George Herbert Mead and the cognitive linguist Noam Chomsky both investigated the nature of language and mind during the 20th century. They approached the issues broadly, pursuing both philosophical and scientific lines of reasoning and evidence. This comparative analysis of Mead and Chomsky identifies fourteen questions that summarize their collective effort, and which animated much of the debate concerning language and mind in the 20th century. These questions continue to be relevant to 21st century inquiries. This paper identifies which questions have been resolved and which have not, and discusses each in the context of relevant literature. The net result is a set of questions that inform interdisciplinary‐minded inquiries today into the nature of language and mind.